Acceptance of counseling, voluntary HIV testing and use of prophylactic nevirapine in labour and immediate puerperium at Muhimbili national hospital, Tanzania (Tanzania Medical Journal, 2007)
Background: Mother to child transmission contributes significantly to the incidence of HIV in our country. A PMTCT program exists in Muhimbili National Hospital (MNH) and some surrounding public hospitals since 2000. Inspite of this it has been observed that a substantial number of women delivering at MNH have not had VCT and therefore cannot benefit from the PMTCT intervention.Objective: To determine the acceptance of counseling, voluntary HIV testing and prophylactic use of Nevirapine among pregnant women during labour / immediate postpartum at Muhimbili National Hospital. Methodology: This descriptive Cross-sectional study was done in the labour ward of MNH. Data collection: Trained counselors invited all women who met inclusion criteria as they were admitted. Patients who had obstetric complications were excluded. Women who accepted counseling were taken to private rooms for discussion and those who consented were screened for HIV using rapid tests. Direct observed therapy with Nevirapine was done. Data was filled in a structured questionnaire and analysed by EPI Info 6 and SPSS software.Results: We recruited 885 women with unknown sero-status through convenient sampling. The overall acceptance of pre-test counseling in labour among women with unknown sero-status was 71.7% while acceptance of counseling and voluntary HIV testing was 56.6%. Among those who accepted pre-test counseling in labour, 78.9% accepted HIV testing and 8.6% of these were found to be HIV infected. Eighty-three percent of women diagnosed to be HIV infected accepted Nevirapine. Counselor's experience of more than 3 years had a significant impact on acceptance of counseling and testing of HIV in labour.Conclusion and recommendation: The results of this study show that HIV testing during labour and use of prophylactic ARV is acceptable in our setting. Women with unknown serostatus in labour should be offered counseling and testing in order to prevent MTCT of HIV. Keywords:Acceptance, HIV testing in labour. Tanzania Medical Journal Vol. 21 (1) 2006: pp. 1-5